The variability of the surface CO2 system and air-sea exchange in the Northeast Atlantic based on VOS data - Curbelo Hernández, David; González Dávila, Melchor; Gonzalez Santana,David; González González, Aridane; Santana-Casiano, J. Magdalena (Servicio de Publicaciones y Difusión Científica de la Universidad de Las Palmas de Gran Canaria (ULPGC), 2023)
The seasonal and spatial variability of the CO2 system parameters and air-sea CO2 exchange was studied in the Northeast Atlantic through the Northwest African coastal transitional area between the Canary Islands and the Strait of Gibraltar. High spatio-temporal resolution data were collected by a Surface Ocean Observation Platform (SOOP) aboard a volunteer observing ship (VOS) from February 2019 to February 2020. The variability of the CO2 fugacity in seawater (fCO2,sw) was strongly driven by the seasonal pattern of the sea surface temperature (SST), which increased with latitude and was lower throughout the year in the high-intense coastal upwelling areas. The fCO2,sw increased from winter to summer by 11.84 ± 0.28 μatm ºC-1 in the Canary archipelago and by 11.71 ± 0.25 μatm ºC-1 along the northwest African continental shelf. The thermal to non-thermal effect ratio (T/B) was approximately 2, with minimum values along the African coastline explained by higher biological activity in the upwelled waters. The factors controlling the seasonality of total inorganic carbon (CT) normalized to constant salinity of 36.7 (NCT) were assessed. The effect of net community production on NCT between February and October represented >90% of the reduction of inorganic carbon while air-sea CO2 exchange described <6%. The seasonality of air-sea CO2 fluxes was driven by SST fluctuations. The surface waters of the entire region acted as a strong CO2 sink during the cold months and as a weak CO2 source during the warm months. A net annual CO2 sink behaviour was observed in both the Canary basin (-0.26 ± 0.04 mol C m-2 yr-1) and the northwest African continental shelf (-0.48 ± 0.09 mol C m-2 yr-1). The calculated average CO2 flux for the entire area in the Northeast Atlantic was -2.65 ± 0.44 Tg CO2 yr-1 (-0.72 ± 0.12 Tg C yr-1). 33 1